The The Actualization of Internal Control for Official Travel : Agency X City A - Barutu, Yuliana Endang; Ginting, Yoremia Lestari (UNKLAB Business School, 2026)
This study aims to explore the forms of internal control activities for official travel at Agency X. It uses a qualitative method with a descriptive approach. Data was collected through observation, interviews, and documentation during an internship at the agency, then analyzed useinh the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The result show that the implementation of internal control over official trave at Agency X was carried out through six aspects of control activities: establishment of responsibilities, separation of duties, documentation procedures, physical controls, independent internal verification, and human resource controls. Additionally, there are supplementary policies such control system is functioning quite well, although weaknesses still exist in employee discipline and the completeness of accountability documents. This study concludes that internal control of official travel plays a vital role in improving the transparency, accountability, and efficiency of regional financial management. Therefore, strengthening employee discipline, optimizing digital systems, and conducting periodic eveluations are crucial to prevent potential irregularities and enhance the quality of government governance.